2011
DOI: 10.1103/physreva.83.062510
|View full text |Cite
|
Sign up to set email alerts
|

Quasibound states in a chaotic molecular system

Abstract: We show the influence of stable and unstable periodic orbits on the energy eigenstates of the HOCl molecule, both below and above dissociation. The energy range considered is low enough to hold the HO bond fixed, allowing a two-dimensional model of the molecule. Above dissociation unstable periodic orbits, in a chaotic sea, anchor quasibound states of the molecule. Quasibound states are calculated using reaction matrix theory and are found to have lifetimes ranging over five orders of magnitude.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The vibrational motion of small molecules, such as HOCl, provides a laboratory for studying the quantum-classical correspondence (QCC) in coupled nonlinear oscillator systems. In a previous paper [17], we studied the QCC using the 2D model of the HOCl molecule. We found that bound states in the quantum system lie primarily on classical periodic orbits, while quasibound states are supported by unstable classical periodic orbits in the continuum.…”
Section: Discussionmentioning
confidence: 99%
“…The vibrational motion of small molecules, such as HOCl, provides a laboratory for studying the quantum-classical correspondence (QCC) in coupled nonlinear oscillator systems. In a previous paper [17], we studied the QCC using the 2D model of the HOCl molecule. We found that bound states in the quantum system lie primarily on classical periodic orbits, while quasibound states are supported by unstable classical periodic orbits in the continuum.…”
Section: Discussionmentioning
confidence: 99%
“…The reaction region is coupled to the asymptotic region with a singular coupling [31,32]. It is useful to note that W-E scattering theory more recently has also been used to analyze electron scattering in quasi-one-dimensional waveguides [33,34], for analyzing the dissociation of the HOCl molecule [36], and for scattering of waves from systems with cylindrical symmetry [37,38]. The procedure is well described in [35,39], so we only outline the steps here.…”
Section: Reaction Matrix For the Bloch Channelsmentioning
confidence: 99%
“…Periodic orbits provide a pathway along which a quantum wave can constructively interfere with itself and thereby create a bound or quasibound quantum state. The connection between classical periodic orbits and quantum bound and quasibound states is well established for 2D systems [5,7], and there is evidence [4] that a similar correspondence exists for systems with three degrees of freedom (3D).…”
Section: (A)mentioning
confidence: 99%
“…The 3D B 0 stable periodic orbit, and its unstable Short periodic orbits, such as the 2D and 3D B 0 periodic orbits serve as organizing centers for large regions of the dynamics, and play an important role in the vibrational quantum dynamics of the molecule. References [5,6] showed that such periodic orbits in 2D HOCl form the backbone of bound We can use the above information about the 3D B 0 orbit to make some predictions about the quantum behavior of the orbit. We have found that the stable 3D periodic orbit B 0 exists over the whole energy interval E≈1.…”
Section: Periodic Orbits Of Hoclmentioning
confidence: 99%
See 1 more Smart Citation